2019
DOI: 10.1155/2019/2306213
|View full text |Cite
|
Sign up to set email alerts
|

Selection and Prioritization of Software Requirements Applying Verbal Decision Analysis

Abstract: During the software development process, the decision maker (DM) must master many variables inherent in this process. Software releases represent the order in which a set of requirements is implemented and delivered to the customer. Structuring and enumerating a set of releases with prioritized requirements represents a challenging task because the requirements contain their characteristics, such as technical precedence, the cost required for implementation, the importance that one or more customers add to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 29 publications
1
11
0
1
Order By: Relevance
“…In previous researches [9][10][11][12], we had good results when we compared the results generated by the Zapros III-i method concerning the SBSE methods. In these works, it was reported that the VDA method is no better than the SBSE methods, but the gain of this research is the opening of this new front in the VDA field, leaving this field as an alternative nonexistent to select and prioritize software requirements.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…In previous researches [9][10][11][12], we had good results when we compared the results generated by the Zapros III-i method concerning the SBSE methods. In these works, it was reported that the VDA method is no better than the SBSE methods, but the gain of this research is the opening of this new front in the VDA field, leaving this field as an alternative nonexistent to select and prioritize software requirements.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, this task in this field is relatively new. The methodology used in this work has already been tested in other scenarios in previous studies [9][10][11][12] and has shown to be efficient to solve qualitatively (VDA) quantitative problems (SBSE) with satisfactory results. For this, it was necessary to create an adaptation methodology for this purpose.…”
Section: Applying the Vda Methodologymentioning
confidence: 99%
See 3 more Smart Citations